CULTURAL VALUES AND BATIK PURCHASE DECISIONS: EXPLORING THE MEDIATING EFFECT OF CONSUMER EMOTIONS - Widiana, Muslichah; Ferrinadewi, Erna (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
Batik, as a cultural artifact, holds deep symbolic and emotional significance; however, declining consumption rates suggest a shift in consumer priorities. This study aims to analyze the mediating role of pride-based emotions both self-focused and object-focused in the relationship between cultural values and Batik purchase decisions in Surabaya, East Java. Adopting a causal quantitative design, data were collected from 207 Batik consumers through a structured survey and analyzed using Structural Equation Modeling (SEM). The results show that while cultural values significantly influence both types of pride emotions, they do not directly affect purchase decisions. In contrast, self-focused and object-focused emotions have a positive and significant impact on purchase behavior and fully mediate the effect of cultural values on Batik buying decisions. These findings suggest that emotions rather than cultural values alone serve as the primary psychological mechanism connecting cultural identity to heritage product consumption. Theoretically, this research highlights the importance of integrating affective variables into cultural consumption models. Practically, Batik producers and marketers are encouraged to develop pride-based emotional branding strategies to enhance consumer engagement. This study introduces the concept of a dual affective pathway, where personal identity and social resonance jointly drive cultural consumption, offering a novel contribution to the cross-cultural consumer behavior literature.